Enhancer interaction networks as a means for singular olfactory receptor expression - Markenscoff-Papadimitriou, Eirene (Cell, 2014)
The transcriptional activation of one out of ~2800 olfactory receptor (OR) alleles is a poorly understood process. Here, we identify a plethora of putative OR enhancers and study their in vivo activity in olfactory neurons. Distinguished by an unusual epigenetic signature, candidate OR enhancers are characterized by extensive interchromosomal interactions associated with OR transcription and share the similar pattern of transcription factor footprints. In particular, we establish the role of the transcription factor Bptf as a facilitator of both enhancer interactions and OR transcription. Our observations agree with the model whereby OR transcription occurs in the context of multiple interacting enhancers. Disruption of these interchromosomal interactions results in weak and multigenic OR expression, suggesting that the rare coincidence of numerous enhancers over a stochastically chosen OR may account for the singularity and robustness in OR transcription.